2012
DOI: 10.1186/1471-2180-12-67
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide excision repair (NER) system of Helicobacter pylori: Role in mutation prevention and chromosomal import patterns after natural transformation

Abstract: BackgroundExtensive genetic diversity and rapid allelic diversification are characteristics of the human gastric pathogen Helicobacter pylori, and are believed to contribute to its ability to cause chronic infections. Both a high mutation rate and frequent imports of short fragments of exogenous DNA during mixed infections play important roles in generating this allelic diversity. In this study, we used a genetic approach to investigate the roles of nucleotide excision repair (NER) pathway components in H. pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Such variations in recombination rates have been previously described between lineages of S. enterica (32), E. coli (36), or Chlamydia trachomatis (37). For H. pylori, laboratory experiments have shown that recombination rates depended significantly on the combination of recipient and donor strains (11,13). Here, however, there seemed to be no relationship between infecting strain and effect of recombination.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Such variations in recombination rates have been previously described between lineages of S. enterica (32), E. coli (36), or Chlamydia trachomatis (37). For H. pylori, laboratory experiments have shown that recombination rates depended significantly on the combination of recipient and donor strains (11,13). Here, however, there seemed to be no relationship between infecting strain and effect of recombination.…”
Section: Discussionsupporting
confidence: 57%
“…This mechanism has been well studied through laboratory experiments (11)(12)(13). In vivo, extensive recombination was first detected by comparison of the phylogenetic signals of three gene fragments (14).…”
mentioning
confidence: 99%
“…Mutants in nucleotide excision repair genes uvrA, uvrB, uvrC and uvrD have been constructed in H. pylori [49,72,73] and their UV sensitivity phenotype confirmed their role in DNA repair.…”
Section: Dna Repair and Mutagenesismentioning
confidence: 88%
“…The scope of this chapter is to review H. pylori genetic and epigenetic plasticity and discuss the hypothesis that this plasticity promotes H. pylori adaptation to individual human hosts by generating phenotypically diverse populations. Emphasis has been put on mathematical modelling of H. pylori chronic infection [44], its micro-evolution and related mechanisms for the generation of diversity including genetic [45][46][47][48][49] and epigenetic diversity [50,51]. Mechanisms of horizontal gene transfer and the generation of intra-strain genetic diversity are reviewed and the implication of phasevarion-mediated epigenetic diversity is discussed in the context of bacterial population and adaption.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori strains were cultured on blood agar plates (41), or in liquid cultures as described (9). Microaerobic conditions were generated in airtight jars (Oxoid, Wesel, Germany) with Anaerocult C gas producing bags (Merck, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%